(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
India has a rich intellectual and also a textual heritage that dates back to several hundreds of years. India culminates one of the largest collections of medical manuscripts of any civilization in the world. The different types of manuscripts in ISM (Indian System of Medicine) includes, Ayurveda that is spread all over India since antiquity along with Siddha this is mainly confined to South India, so rig-pa, which is confined to Tibetan plateau and Unani-Tibb this is Greco-Arabian system of medicine, which came to India along with the Muslims. A proper understanding in the review of ancient manuscripts revealed that the past existence of medical manuscripts evidences were available mainly in four forms those were Bhurja patra (palm leaves), old handmade paper and commonly available paper. The review also revealed that presently available medical texts, which are in use now, represents less than 2% of medical literature which are in use now, information which are now lost that were present in the manuscript. The location of the manuscripts are in archaeological departments, National libraries etc. The only attempt to catalogue Indian Medical Literature was preferred by Osmania University in 1958. There is utmost urgency for conservation of medical manuscripts to revive ancient knowledge for health and prosperity as there is a great threat in losing the manuscripts due to negligence. The intellects achievements of Indian culture lay scattered across several fields of study in ancient texts ranging from Vedas to Upanishads to a whole culmination of scriptures, science and arts thus signalling an urgent need in reviving these manuscripts.